Co-axial carbon nanotubes and Ni-Si nanowire as anode material for high performance Li Ion battery - Chen, Ivan Weide. (2013)
In this technological advanced age, electronic gadgets have become necessities and its services have been embedded into our daily life routine. However with miniaturization for better mobility and the increasing additional features, battery life for performance had since been deteriorating. Si, with its higher theoretical specific capacity, has been investigated for the replacement of the conventional anode material of the widely used Li ion battery.